La mairie de Londres et la décentralisation : entre autonomie et indépendance - Timothy Whitton (Revue Française de Civilisation Britannique)
In its 1992 manifesto the Labour Party considered setting up a municipal authority in London. Empowering a pan-London authority was part and parcel of Labour’s global programme of modernisation, one of the outstanding leitmotifs of the third way. But these plans did not take Kenneth Livingstone sufficiently into account. “Red” Ken still championed some of the collectivist values cherished by Old Labour which Blair and his friends would like to have once and for all consigned to the history of the Labour party. Taking full advantage of his popularity as a candidate and then as elected mayor, Livingstone was determined to make sure that the Greater London Authority should not be subjected to the will and whims of central government. At the outset, remaining faithful to his Greater London Council ways, Livingstone personified opposition to central government. His second victory in June 2004, on the other hand, was the opportunity for Londoners to judge their mayor and municipal authority according to their track record.